The Inheritance of the Pheromone Sensory System in Two Helicoverpa Species: Dominance of H. armigera and Possible Introgression from H. assulta - Xu, Meng; Dong, Jun-Feng; Wu, Han; Zhao, Xin-Cheng; Huang, Ling-Qiao; Wang, Chen-Zhu (Frontiers in Cellular Neuroscience, 2017)
Hybridization of sympatric closely related species may sometimes lead to introgression and speciation. The sister species Helicoverpa armigera and Helicoverpa assulta both use (Z)-11-hexadecenal and (Z)-9-hexadecenal as sex pheromone components but in reversed ratios. Female H. armigera and male H. assulta could hybridize and produce fertile male hybrids, which can then backcross with females of the two parent species to get backcross lines in the laboratory. In this study, we compared the olfactory responses to pheromone compounds in the periphery and in the antennal lobes of males of the two species, as well as of their hybrids and backcrosses. Single-sensillum recordings were carried out to explore characteristics of male-specific sensilla in antennae, and in vivo calcium imaging and digital 3D-reconstruction were used to describe what happens in the macroglomerular complex (MGC) of antennal lobes. The results show that the population ratio of the two olfactory sensory neurons responding to two sex pheromone components in male antennae are controlled by a major gene, and the allele of H. armigera is dominant. Consistently, the study of the representative areas activated by sex pheromone components in antennal lobes further support the dominance of H. armigera in pheromone detection. However, the topological structure of the MGC in the hybrid was similar but not identical to that in H. armigera. All the subtypes of male-specific sensilla in the two species were found in the male hybrids and backcrosses. Moreover, two new subtypes with broader response spectra (the expanded A subtype and the expanded C subtype) emerged in the hybrids. Based on the inheritance pattern of the pheromone sensory system, we predict that when hybridization of female H. armigera and male H. assulta occurs in the field, male hybrids would readily backcross with female H. armigera, and introgression might occur from H. assulta into H. armigera through repeated backcrossing.